Bridging Financial Reporting Research and Policy: A Discussion of 'The Impact of Accounting Standards on Pension Investment Decisions'. Issue 1 (1st January 2019) - Cascino, Stefano
Abstract: Barthelme, Kiosse, and Sellhorn (2018. The impact of accounting standards on pension investment decisions. European Accounting Review . doi:10.1080/09638180.2018.1461670 ) examine the real effects of pension accounting regulation and provide evidence consistent with the claim that recent changes in financial reporting rules affect pension asset allocation decisions. Their study offers an interesting opportunity to highlight the importance of evidence-based policymaking in the field of financial reporting. I discuss some empirical challenges that the authors face to causally identify the effects they examine to show how a closer cooperation between academia and regulators can enable researchers to overcome identification challenges and help produce even more policy-relevant research.